P147 Trends in choice of first line biologic therapy for patients with Inflammatory Bowel Disease. An observational cohort study. (30th January 2023) - Fernando, S; Abu-Rgeef, R; Menon, S; So, K; Venugopal, K; Picardo, S
Abstract: Background: Biologic therapies have revolutionised the management of Inflammatory Bowel Disease (IBD) with increasing utilisation over the last decade. The anti-Tumour Necrosis Factor-alpha (anti-TNF) agents (Infliximab (IFX) and Adalimumab (ADA)) as well as newer agents (Ustekinumab (UST) and Vedolizumab (VED)) all have well demonstrated safety and efficacy profiles in the management of IBD. The choice of an optimal first line biologic remains unclear due to lack of comparative randomised trials and real-world studies; however, certain patient and disease characteristics may influence this choice. The aims of this study were to explore temporal trends in choice of 1 st -line biologic therapy and factors that influence this choice. Methods: A retrospective observational cohort study of all patients with IBD that commenced induction and completed at least one maintenance dose of a biologic therapy between 1 st January 2015 and 31 st December 2021. Relevant patient and disease-specific factors were collected, including patient comorbidities (ischaemic heart disease, malignancy and opportunistic infections) at time of diagnosis, for each eligible patient. Factors affecting choice of biologic therapy were compared using ANOVA and c2 test. Results: 280 patients were included, with 50.7% being male and median age of IBD diagnosis of 29 years. There was a progressive increase in biologic use over time, with 15 patients commencing1 st biologic therapy in 2015, rising to 58 patients in 2021. UST has overtaken IFX and ADA as first line choice for Crohn's disease (CD) since its introduction in 2018 (Figure 1). IFX has remained preferred first line therapy for ulcerative colitis (UC) over VED and ADA, with stable trend in choice over time. Factors with significant differences in choice of first line biologic therapy included age (UST for older age of commencement), IBD subtype (higher proportion of patients commencing ADA had CD, whereas higher proportion of patients commencing VED had UC), disease location (VED was preferred for colonic over ileal CD), and malignancy (UST was preferred) (Table 1). Conclusion: - There has been a steady rise in the number of patients commencing biologic therapies, with an average increase of 24% per year from 2015 to 2021. - Ustekinumab has replaced anti-TNF therapy as the preferred first line biologic for Crohn's disease; a trend likely secondary to the comparatively favourable safety profile of ustekinumab. Ustekinumab was preferred in older patients and those with history of malignancy. - Infliximab remains the preferred first line therapy for ulcerative colitis with stable trends in choice. - The presence of perianal disease was not a significant factor affecting choice.